The function of phytogenic mounds in the accumulation and conservation of soil seed banks in semiarid areas with water erosion - Nie, W. J.; Du, H. D.; Xie, S. S.; Bi, Y. L. (Frontiers in Environmental Science, 2024)
Background Phytogenic mounds are a type of microtopography formed under perennial plants canopies in water erosion areas. However, the function of phytogenic mounds in seed assemblages and their ecological consequences remain poorly understood in semiarid areas with water erosion. Thus, understanding the characteristics of seed banks on mounds is crucial for ecosystem conservation and management in water-eroded areas. Methods We compared the quantity and composition of soil seed banks on the upslope and downslope parts of mounds and intercanopy surfaces along four slope gradients. We also explored the relationships among the soil seed bank, aboveground vegetation, and environmental factors. Furthermore, the species similarity between the soil seed bank and aboveground vegetation was analyzed to clarify the important ecological consequences of phytogenic mounds for plant community construction in serious soil erosion area. Results For slopes with α ≤ 46.6%, the intercanopy surfaces had greater soil seed bank species composition, density, and diversity than did the phytogenic mounds, and these characteristics showed no significant differences between the upslope and downslope parts of the mounds. As the slope increased, the soil seed bank density and species composition increased on the upslope part of the mound, and reached a maximum for slopes with α > 70%, while the downslope part of the mound negatively effected on seed aggregation. The sediment accumulation rate, soil moisture, particle size distribution, pH, organic matter carbon, and hardness were significantly correlated with the soil seed bank density and diversity in the study area. For slopes with 0 < α ≤ 26.8%, the species similarity coefficient between the soil seed bank and aboveground vegetation was the highest for the intercanopy surface. This species similarity on the upslope part of the mound showed an increasing trend with increasing slope gradient, while the downslope part of the mound had the opposite trend. For slopes with α > 70%, the upslope part of the mound did not only have more species in the soil seed bank but also had more species in aboveground vegetation than did the downslope part of the mound and intercanopy surface. Conclusion For slopes with α ≤ 46.6%, phytogenic mounds had barely impact soil seed bank accumulation and conservation in semiarid and eroded areas. For slopes with α > 46.6%, the mounds (particularly on the upslope part of the mound) showed seed assemblage functions, which are coupled with improving edaphic conditions and decreasing microhabitat stress; thus, phytogenic mounds, or areas of microtopography, can be used to promote restoration success in semiarid eroded areas.